2020
DOI: 10.1002/pip.3239
|View full text |Cite
|
Sign up to set email alerts
|

Development and outdoor characterization of a hybrid bifacial HCPV module

Abstract: Conversion of direct, diffuse, and albedo irradiance into electricity is demonstrated with a new kind of hybrid bifacial high‐concentration photovoltaic module named bifacial EyeCon. It consists of Fresnel lenses that concentrate the direct sunlight 321x onto III‐V triple‐junction solar cells that are mounted on the front surface of p‐PERC bifacial c‐Si cells. Thus, the Si absorbs the front and rear diffuse irradiance. Because III‐V and Si cells are electrically isolated (hence a 4‐terminal device) but thermal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 14 publications
(17 reference statements)
0
8
0
1
Order By: Relevance
“…The perspective has motivated several groups to explore the idea in various realizations: III-V cells located in-between spaced Si cells, 14 mounted on a transparent substrate above the Si cells, [14][15][16] or directly mounted on top of the Si cell. 5,12,17,18 Hybrid Insolight modules initially took the first approach. The aspherical coefficients that define the shape of the biconvex lens were optimized using ray-tracing simulations in order to maximize simultaneously the amount of direct light concentrated on a 1-mm triple-junction cell and the amount of diffuse installed.…”
Section: Hybrid Iii-v/si Architecturementioning
confidence: 99%
See 1 more Smart Citation
“…The perspective has motivated several groups to explore the idea in various realizations: III-V cells located in-between spaced Si cells, 14 mounted on a transparent substrate above the Si cells, [14][15][16] or directly mounted on top of the Si cell. 5,12,17,18 Hybrid Insolight modules initially took the first approach. The aspherical coefficients that define the shape of the biconvex lens were optimized using ray-tracing simulations in order to maximize simultaneously the amount of direct light concentrated on a 1-mm triple-junction cell and the amount of diffuse installed.…”
Section: Hybrid Iii-v/si Architecturementioning
confidence: 99%
“…Moreover, the laminate is compatible with bifacial Si cells, which can capture albedo from the surroundings. The benefits of using bifacial Si cells in a hybrid CPV/PV architecture were discussed by Martínez et al 17 The energy gains associated will be further discussed in Section 3.3.…”
Section: Hybrid Iii-v/si Architecturementioning
confidence: 99%
“…Notably, these values remain below those of conventional CPV modules ( η < 38.9%) 7 because their calculation is based on GNI instead of DNI. Nevertheless, it has been demonstrated that hybrid devices are able to generate between 3.5% and 30.6% more power, relative to their CPV part, when the DNI/GNI ratio is between 92% and 57%, respectively 2,8 …”
Section: Introductionmentioning
confidence: 99%
“…Both modules concentrate DNI 321 times with a 4 × 12 array of silicone‐on glass Fresnel lenses where a single lens has a size of 4.76 × 4.76 cm 2 . Additionally, the 48 CPV cells are mounted with a dielectric adhesive onto the top surface of a flat‐plate PV array of eight bifacial positively doped passivated emmiter rear contact (p‐PERC) c‐Si solar cells 8,22 . This enables the flat‐plate PV cells to act as heat distributors for the CPV cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation